What Determines the Capital Adequacy Ratio of Joint Venture Commercial Banks of Nepal? An Evidence from Panel Data Analysis - Purna Man Shrestha (MASI Mandiri Edukasi, 2023)
The bank with the appropriate capital adequacy ratio (CAR) is considered the more substantial bank that can meet its obligations and take risks. Thus, the bank management has to identify those factors influencing CAR. This study aims to identify the factors determining the CAR of commercial banks in Nepal. For this purpose, this study has used annual panel data of 6 joint venture commercial banks of Nepal from 2007 to 2021. This paper's regression analysis revealed that bank-specific factors significantly determine the capital adequacy ratio. Further, the study concluded that the financial performance measured by ROE and lending policy measured by the ratio of the total loan and advance to total assets (LTA) plays an inverse role. Liquidity LTD), management efficiency (ME), operational efficiency (OE), and the size of the bank (SIZE) play a positive role in determining the capital adequacy ratio.Â The bank's management can implement the findings of this paper to maintain a sufficient capital adequacy ratio. Further, the finding of this study can also be implemented by the regulatory bodies to develop policies relating to the capital requirements of commercial banks.